Participation of abscisic acid and gibberellins produced by endophytic Azospirillum in the alleviation of drought effects in maize - Cohen, Ana Carmen (2009)
Azospirillum spp. are plant growth promoting bacteria (PGPB) that enhance growth by several mechanisms, including the production of phytohormones such as abscisic acid (ABA), indole-3-acetic acid (IAA), and gibberellins (GAs). Their presence may also alleviate plant water stress. In the present paper, the effects of Azospirillum lipoferum in maize (Zea mays L.) plants treated with inhibitors of ABA and GA synthesis, fluridone (F) and prohexadione-Ca (P), respectively, and either submitted to drought stress or provided sufficient water, were analysed. Fluridone diminished the growth of plants that had been well watered, in a manner similar to drought, but inoculation with Azospirillum completely reversed this effect. The relative water content of the F-treated and drought-stressed plants was significantly lower (even though drought-stressed plants had been allowed to recover for one week), and this effect was completely neutralized by Azospirillum. These results were correlated with ABA levels assessed by GC-EIMS. Growth was diminished in droughtsubmitted plants treated with P, alone or combined with F, even though ABA levels were enhanced, suggesting that Gas produced by the bacterium are also important in stress alleviation. The results suggest that both ABA and GAs contribute to water-stress alleviation of plants by Azospirillum.